Calibration and validation of the Pneumonia Shock Score in critically ill patients with SARS-CoV-2 infection, a multicenter prospective cohort study - Carmo, Thomas A.; Ferreira, Isabella B. B.; Menezes, Rodrigo C.; Pina, Márcio L. T.; Oliveira, Roberto S.; Telles, Gabriel P.; Machado, Antônio F. A.; Aguiar, Tércio C.; Caldas, Juliana R.; Arriaga, María B.; Akrami, Kevan M.; Filgueiras Filho, Nivaldo M.; et al. (Frontiers in Medicine, 2022)
Background: Prognostic tools developed to stratify critically ill patients in Intensive Care Units (ICUs), are critical to predict those with higher risk of mortality in the first hours of admission. This study aims to evaluate the performance of the pShock score in critically ill patients admitted to the ICU with SARS-CoV-2 infection. Methods: Prospective observational analytical cohort study conducted between January 2020 and March 2021 in four general ICUs in Salvador, Brazil. Descriptive statistics were used to characterize the cohort and a logistic regression, followed by cross-validation, were performed to calibrate the score. A ROC curve analysis was used to assess accuracy of the models analyzed. Results: 605 adult ICU patients were included in the study. The median age was 63 (IQR: 49 - 74) years with a mortality rate of 33.2% (201 patients). The calibrated pShock-Cov score performed well in prediction of ICU mortality (AUC of 0.80 [95% Confidence Interval (CI): 0.77 - 0.83; p-value<0.0001]. Conclusions: The pShock-Cov score demonstrated robust discriminatory capacity and may assist in targeting scarce ICU resources during the COVID-19 pandemic to those critically ill patients most likely to benefit.